Pola Komunikasi Kelompok Halaqah Dalam Membentuk Karakteristik Islami Mahasiswa Melalui Lembaga Dakwah Al-Izzah UIN Sumatera Utara - Rangkuti, Nurul Izzah; Samosir, Hasrat Efendi (Jayapangus Press, 2024)
Halaqah aims to form Islamic characteristics in each individual at the North Sumatra State Islamic University. This research uses qualitative research with a descriptive approach. The subjects of this research were 4 (four) heads of the halaqah group of the UINSU Campus Da'wah Institute. The supporting informants in this research were 4 (four) individuals other than the subjects studied, namely members of the halaqah group of the UINSU Campus Da'wah Institute. The research was conducted at the North Sumatra State Islamic University, Faculty of Da'wah and Communication. Data collection techniques were obtained through observation, interviews and documentation. The data analysis technique uses domain analysis which is carried out starting from reducing data, presenting data, and drawing conclusions. Research findings have shown that many UINSU students still have characters that do not reflect Islamic character, starting in terms of dress, manners or other things that are influenced by various internal and external factors. Halaqah as an alternative for building Islamic character through group communication patterns. Halaqah is a primary communication pattern through materials presented by the group leader. Although several factors influence the character of students, there are several ways that halaqah leaders can do to form an Islamic character in terms of being polite and courteous towards elders and others, resulting in even better harmony of brotherhood. This communication pattern is one of the efforts or suggestions for the campus and students to continue to support this halaqah activity to continue to develop students in a better direction. The communication carried out can form a character who can carry out Islamic values ​​in daily life such as better behavior patterns such as etiquette in meeting and interacting between the opposite sex and being more diligent in praying.